Outcome of Segmental Thoracic Spinal Anaesthesia in Laparoscopic Cholecystectomy - Kamal, Md Mostafa; Afroz, Shahara; Amin, Md Ruhul; Islam, Md Shahidul; Akhtaruzzaman, AKM (International Journal of Human and Health Sciences (IJHHS), 2025)
Background: Segmental thoracic spinal anaesthesia has been used in different surgeries. This regional anaesthesia technique could be a potential alternative to general anaesthesia for laparoscopic cholecystectomy. Objective: To assess the outcome of segmental thoracic spinal anaesthesia in laparoscopic cholecystectomy. Methods: This study was conducted at surgery operation theatre in the Shaheed Suhrawardy Medical College Hospital, Dhaka, Bangladesh, from February to April, 2023. Patients aged between 18 and 40 years with ASA class I or II undergoing elective laparoscopic cholecystectomy were included. Segmental thoracic spinal anaesthesia was performed at T10 intervertebral space with injection 0.5% hyperbaric bupivacaine 1 ml (5mg) and fentanyl 0.5 ml (25 microgram). Perioperative hemodynamic changes, side effects, time of first rescue analgesic, total opioid consumption in first 24 h, patient and surgeon satisfaction score were recorded. Results: A total of 30 patients received thoracic segmental spinal anaesthesia and none of them required conversion to general anaesthesia. The mean age of the patients was 29.89 ± 8.5 years. Maximum patients 21 (70%) belongs to ASA Class I. Two patients experienced paraesthesia during insertion of spinal needle and subsided by slight withdrawal of the needle without any adverse sequelae. They were observed for a period of one month and no post procedural sequelae was found. Average duration of surgery was 48.20±9.7 minutes. There were no clinically significant hemodynamic changes during the perioperative period. Five patients (16.6%) experienced shoulder pain. The time of 1st analgesic was 3.8±1.2 hours and total dose of opioid consumption was 70.68±12.7 mg in first 24 hours. Both patients (53%) and surgeons (60%) were satisfied with this technique. Conclusion: Laparoscopic cholecystectomy can be done effectively by segmental thoracic spinal anaesthesia technique. It can be considered as an alternative to general anaesthesia but great caution is required to avoid injury to the spinal cord during needle insertion. International Journal of Human and Health Sciences Vol. 09 No. 02 Apr’25 Page: 113-118